Training about dental prenatal for professionals in the health team: experience report (Research, Society and Development, 2020)
Objective: To report the development of training, for health team professionals, about the importance of dental prenatal care. Method: Experience report on building a training on a distance education platform (EAD), aiming to instruct, prepare and motivate these professionals to encourage pregnant women to perform dental prenatal care by demystifying the beliefs and myths that involve it. Results: The tool created equips the health team professionals about the theme and motivates them to carry out an interdisciplinary approach to patients, encouraging them to perform dental prenatal care, as they know its importance. In addition, the fact of being distance education, provides an expanded access to the knowledge provided. Final Considerations: The construction of structured technologies on dental prenatal care for the health team may contribute so that the professionals involved in prenatal care can develop the necessary skills to be agents that promote dental monitoring during pregnancy, impacting the expansion of use of dental services by pregnant women and consequently in the well-being of the mother-baby binomial.